2008
DOI: 10.1007/s00607-008-0018-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of hierarchical matrices for computing the Karhunen–Loève expansion

Abstract: Realistic mathematical models of physical processes contain uncertainties. These models are often described by stochastic differential equations (SDEs) or stochastic partial differential equations (SPDEs) with multiplicative noise. The uncertainties in the right-hand side or the coefficients are represented as random fields. To solve a given SPDE numerically one has to discretise the deterministic operator as well as the stochastic fields. The total dimension of the SPDE is the product of the dimensions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 38 publications
0
96
0
Order By: Relevance
“…The kernel is chosen to be a member of the Matérn covariance family, the exponential covariance kernel κ(x, y) = exp(− x − y /l), where l is the integral length scale and is chosen to be 1. It can be shown that this kernel satisfies the requirements of asymptotic smoothness [33] as stated in Section 2. We also make the following choices for the parameters: we pick η = 0.75 and n min = 32.…”
Section: H-matrix Approximation Of Covariance Matricesmentioning
confidence: 88%
See 1 more Smart Citation
“…The kernel is chosen to be a member of the Matérn covariance family, the exponential covariance kernel κ(x, y) = exp(− x − y /l), where l is the integral length scale and is chosen to be 1. It can be shown that this kernel satisfies the requirements of asymptotic smoothness [33] as stated in Section 2. We also make the following choices for the parameters: we pick η = 0.75 and n min = 32.…”
Section: H-matrix Approximation Of Covariance Matricesmentioning
confidence: 88%
“…In terms of applications, it is useful to consider three kinds of covariance kernels [33]: 1. isotropic and translation invariant, i.e., κ(x, y) = κ(|x−y|); 2. stationary and anisotropic, i.e., κ(x, y) = κ(x − y); 3. non-stationary. Some possible choices for the covariance kernel κ(·, ·) arise from the Matérn family of covariance kernels [34], corresponding to a stationary and isotropic stochastic process.…”
Section: Covariance Functionsmentioning
confidence: 99%
“…However, in the presence of round-off errors, these quantities are not numerically zero. We compare the results for three different covariance kernels defined in (15) and we have A = M QM and B = M . The results are summarized in Table II.…”
Section: Accuracy Of Qr With Weighted Inner Productmentioning
confidence: 99%
“…To demonstrate the effect of correlation length l on the accuracy of the randomized calculations, we consider the following numerical experiment. The eigenvalues are computed for the KLE using the covariance kernel κ ν=5/2 as defined in Equation (15). The domain for the computations is [−1, 1] and the number of grid points are 501.…”
Section: Effect Of Correlation Length Lmentioning
confidence: 99%
See 1 more Smart Citation